2022
DOI: 10.1101/2022.03.07.483255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gliotransmission of D-serine promotes thirst-directed behaviors inDrosophila

Abstract: Thirst emerges from a range of cellular changes that ultimately motivate an animal to consume water. Although thirst-responsive neuronal signals have been reported, the full complement of brain responses is unclear. Here we identify molecular and cellular adaptations in the brain using single-cell sequencing of water deprived Drosophila. Water deficiency primarily altered the glial transcriptome. Screening the regulated genes revealed astrocytic expression of the astray-encoded phosphoserine phosphatase to bi-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 178 publications
1
5
0
Order By: Relevance
“…Due to the heterogeneity in the size and shape of glial cells, adult fly brain cells were suspended into single cells and sorted by the criteria whether the cells express GFP (Figure 1B). Interestingly, the sorting plot revealed that 8-10% of total cells were GFP-positive, correlating with the reported number of glia in adult fly brains (Croset et al, 2018;Brunet Avalos et al, 2019;Park et al, 2022). After removal of cell debris, single GFP-positive glial cells were visualized by confocal microscopy (Figure 1C).…”
Section: Purification and Rna-sequencing Analysis Of Adult Fly Glia E...supporting
confidence: 65%
See 1 more Smart Citation
“…Due to the heterogeneity in the size and shape of glial cells, adult fly brain cells were suspended into single cells and sorted by the criteria whether the cells express GFP (Figure 1B). Interestingly, the sorting plot revealed that 8-10% of total cells were GFP-positive, correlating with the reported number of glia in adult fly brains (Croset et al, 2018;Brunet Avalos et al, 2019;Park et al, 2022). After removal of cell debris, single GFP-positive glial cells were visualized by confocal microscopy (Figure 1C).…”
Section: Purification and Rna-sequencing Analysis Of Adult Fly Glia E...supporting
confidence: 65%
“…F/F was calculated by fluorescence after addition of neurotransmitter subtracting the baseline fluorescence level (Tian et al, 2009;Vicario and Cali, 2019). To eliminate for baseline differences in F/F0 between samples, we normalized the "preconditioning" treatment for each cell to equal 0 (Park et al, 2022).…”
Section: Calcium Imagingmentioning
confidence: 99%
“…ATP can be released via hemichannels, exocytosis, anion channels, and lysosomes (Bezzi and Volterra, 2001;Fujii et al, 2017;Xiong et al, 2018). Lastly, D-serine has been shown to be released via exocytosis, BEST-1, and hemichannels (Wolosker et al, 1999;Martineau et al, 2013;Sild and Van Horn, 2013;Herman, 2018;Koh et al, 2022;Linsambarth et al, 2022;Park et al, 2022;Tapanes et al, 2022). Created with BioRender.com.…”
Section: Glutamatementioning
confidence: 99%
“…Glial D-serine is relevant for astrocytes across multiple species including Drosophila. In Drosophila, glial D-serine is required for thirst-directed behavior (Park et al, 2022). Many studies have shown that astrocytes can release D-serine under pathological conditions.…”
Section: D-serinementioning
confidence: 99%
“…Studies of peripheral wrapping glia uncovered intriguing links between glial-dependent clustering of voltage-gated ion channels and the evolution of myelination (Rey et al, 2023). Shaping higher-order brain functions, astrocytic D-serine gliotransmission promotes thirst-directed behaviors (Park et al, 2022).…”
mentioning
confidence: 99%